2018
DOI: 10.1017/jfm.2018.937
|View full text |Cite
|
Sign up to set email alerts
|

On the dispersion of a drug delivered intrathecally in the spinal canal

Abstract: This paper investigates the transport of a solute carried by the cerebrospinal fluid (CSF) in the spinal canal. The analysis is motivated by the need for a better understanding of drug dispersion in connection with intrathecal drug delivery (ITDD), a medical procedure used for treatment of some cancers, infections and pain, involving the delivery of the drug to the central nervous system by direct injection into the CSF via the lumbar route. The description accounts for the CSF motion in the spinal canal, desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 38 publications
3
61
0
Order By: Relevance
“…We used our recently developed mathematical formulation 10,11 to compute the average Lagrangian bulk motion of solute particles in healthy volunteers. To apply the model, we first obtained from MR imaging measurements all of the input parameters: the subject-specific anatomy of the SSAS, the frequency of the intracranial pressure pulsation, and an estimation of the distribution of compliance (elasticity) of the spinal canal.…”
Section: General Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…We used our recently developed mathematical formulation 10,11 to compute the average Lagrangian bulk motion of solute particles in healthy volunteers. To apply the model, we first obtained from MR imaging measurements all of the input parameters: the subject-specific anatomy of the SSAS, the frequency of the intracranial pressure pulsation, and an estimation of the distribution of compliance (elasticity) of the spinal canal.…”
Section: General Outlinementioning
confidence: 99%
“…As revealed by imaging studies using radionucleotides injected into the SSAS, [6][7][8][9] in addition to the oscillatory flow, there is a steady bulk flow of CSF with much smaller velocities. Our recent studies 10,11 combining multiscale asymptotic analyses of the Navier-Stokes equations with controlled experiments in canonical in vitro models of the SSAS have shed light on the physical mechanisms responsible for the establishment of this slow bulk motion. In particular, it has been shown that in addition to the oscillatory flow with a zero time average, the motion of the fluid particles is affected by a small velocity correction resulting from the combined effects of fluid inertia (the so-called "steady streaming") and spatial gradients of amplitude of the axial pulsation (the socalled "Stokes drift").…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the uniaxial flow in many systems is not steady. For instance, cerebrospinal fluid within a spinal cavity, which can be approximated as an eccentric annulus, moves in a pulsatile, time‐oscillatory manner due to changes in intracranial blood volume during the cardiac cycle . Despite a laminar and zero net bulk flow, oscillatory displacement in a pulsatile flow has been shown to substantially enhance drug dispersion, and is associated with pathological conditions such as hydrocephalus, Chiari malformations, and syringomyelia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a laminar and zero net bulk flow, oscillatory displacement in a pulsatile flow has been shown to substantially enhance drug dispersion, and is associated with pathological conditions such as hydrocephalus, Chiari malformations, and syringomyelia. The needs for a precise control of drug delivery from the lumbar spine to distant target sites in cervical spine or the brain motivated recent development of a drug dispersion model . Pulsatile flows occur naturally in other systems such as fluid flow in a catheterized artery, and have been employed to aid removal of static mud channels during oilfield cementing .…”
Section: Introductionmentioning
confidence: 99%